Diet quality, body weight, and postmenopausal hot flashes: a secondary analysis of a randomized clinical trial - Haley Brennan; Tatiana Znayenko-Miller; Macy Sutton; Richard Holubkov; Neal D. Barnard; Hana Kahleova (BMC, 2024)
Abstract Background A low-fat vegan diet, supplemented with soybeans, has been shown effective in reducing postmenopausal hot flashes. This secondary analysis assessed the association of a plant-based index (PDI), healthful (hPDI), and unhealthful (uPDI), with changes in hot flashes in postmenopausal women. Methods Participants (n = 84) were randomly assigned to a low-fat vegan diet supplemented with soybeans (n = 42) or a control group (n = 42) for 12 weeks. Three-day dietary records were analyzed and PDI indices were calculated. A repeated measures analysis of variance (ANOVA) was used for statistical analysis. Results All three scores increased in the vegan group, compared with no change in the control group; the effect sizes were: PDI + 9.8 (95% CI + 5.8 to + 13.8; p < 0.001); hPDI + 10.9 (95% CI + 6.4 to + 15.3; p < 0.001); and uPDI + 3.6 (95% CI + 0.5 to + 6.6; p = 0.02). The change in all three scores negatively correlated with change in body weight (PDI: r=-0.48; p < 0.001; hPDI: r=-0.38; p = 0.002; and uPDI: r=-0.31; p = 0.01). The changes in PDI and uPDI were negatively associated with changes in severe hot flashes (r=-0.34; p = 0.009; and r=-0.43; p < 0.001, respectively), and associations remained significant after adjustment for changes in body mass index (r=-0.31; p = 0.02; and r=-0.41; p = 0.001, respectively). Conclusions These findings suggest that minimizing the consumption of animal products and oil may be an effective strategy to reduce hot flashes in postmenopausal women, and that categorization of plant foods as "healthful" or "unhealthful" may be unwarranted. Trial registration ClinicalTrials.gov, NCT04587154, registered on Oct 14, 2020.